ICTV Virus Taxonomy Profile: Secoviridae 2022. (2nd December 2022) - Fuchs, Marc; Hily, Jean-Michel; Petrzik, Karel; Sanfaçon, Hélène; Thompson, Jeremy R.; van der Vlugt, René; Wetzel, Thierry
Abstract : Members of the family Secoviridae are non-enveloped plant viruses with mono- or bipartite linear positive-sense ssRNA genomes with a combined genome of 9 to 13.7 kb and icosahedral particles 25–30 nm in diameter. They are related to picornaviruses and are members of the order Picornavirales . Genera in the family are distinguished by the host range, vector, genomic features and phylogeny of the member viruses. Most members infect dicotyledonous plants, and many cause serious disease epidemics. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) report on the family Secoviridae, which is available at ictv.global/report/secoviridae .